Assessing the Moderating Role of Destana Program in Community Resilience and Climate Change - Nadia Makhya Azhari; Rachmadhi Purwana; Kosuke Mizuno (Indonesian Journal of Social and Environmental Issues (IJSEI), 2025)
This study aims to assess Disaster Resilience Village (DESTANA) program has managed to enhance community resilience in the face of climate change impacts in Tambakreja Village, Cilacap Regency. The study utilized primary data collected through questionnaires and employed logistic regression analysis to examine the relationship between climate change, the DESTANA program, and community resilience. The results indicate that the DESTANA program positively impacts community resilience. However, the program's moderating role in the relationship between climate change and community resilience was not significant. This suggests that factors such as program implementation quality, community participation, and local context may influence the program's effectiveness. To enhance the impact of the DESTANA program, future research should explore the role of these factors in greater detail.